An integrated sedimentological-chemostratigraphic study of the Late Devonian-Early Mississipian Chattanooga Formation in Kansas: high-resolution stratigraphy and organic matter accumulation - Brower, Spencer C. (Kansas State University, 2019)
The Chattanooga (Woodford) Formation is an organic-rich, black shale that was deposited in Kansas and Oklahoma during the late Devonian and the upper part of the early Mississippian as a result of a transgressive sequence. It is both a source rock and unconventional hydrocarbon reservoir. This research aimed to produce a high-resolution, sequence stratigraphic framework based on the identification of key stratigraphic surfaces, systems tracts and depositional sequences. The framework was used to infer the processes that controlled sediment accumulation and produced this mudrock succession. The analyses included a centimeter to millimeter scale sedimentological description, aided by petrography and XRD, and the generation of chemostratigraphic profiles using hand-held XRF (HHXRF) point data. A smaller sample set was analyzed using inductively-coupled plasma mass spectrometry (ICP-MS) and LECO carbon/sulfur analyzer. Facies descriptions and HHXRF data were collected by analyzing a core from Douglas County, Kansas. Chemostratigraphic data were used to detect variations in the concentration of specific elements that can provide information on sediment source at the time of deposition, primary productivity and bottom-water oxygen concentrations (anoxic vs. oxygenated). Three depositional sequences, characterized by distinct facies associations and chemostratigraphic signatures, were identified in the studied succession. This study on the Chattanooga (Woodford) Formation suggests that the main control in the accumulation of organic matter was primary productivity. In most instances, anoxia seems to have been driven by the high organic flux. The most favorable conditions for the formation of organic-rich sediments seems to be when high organic flux is accompanied by anoxia (due to increasing water depth), such as recorded in Sequence 3.
Keywords: Chattanooga; Shale; Stratigraphy; Geology